THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, CAPITAL STRUCTURE, AND STOCK PRICE ON FIRM VALUE: (Empirical Study on Banking Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2017-2021) - Indah Majidah; Desi Jelanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
Corporate social responsibility (CSR), capital structure, and stock prices have garnered significant attention due to their potential impact on a firm's overall value. Corporate social responsibility involves a company's commitment to ethical and sustainable practices, extending beyond profit generation to encompass social and environmental considerations. On the other hand, capital structure reflects a company's financing composition, encompassing the balance between debt and equity. Stock prices reflect the market's perception of a company's worth and performance. This research aimed to analyze the influence of corporate social responsibility, capital structure, and stock prices on firm value within the banking sub-sector companies during the period 2017-2021. The study utilized panel data regression as its analytical technique. The sample was selected using purposive sampling from secondary data, specifically financial reports. The analysis included 33 companies observed over a 5-year period, resulting in a total of 165 data points for the investigation. Hypothesis testing was conducted using the Eviews series 9 application. The findings from the tests indicated a statistically significant simultaneous impact of corporate social responsibility, capital structure, and stock prices on firm value. However, the research revealed that corporate social responsibility, when assessed independently, did not exhibit a statistically significant impact on firm value. Conversely, the analyses demonstrated that both capital structure and stock prices had a statistically significant partial effect on firm value.